Phytochemical Composition, Antioxidant, Antiacetylcholinesterase, and Cytotoxic Activities of Rumex crispus L. - Mohamed Marouane Saoudi; Jalloul Bouajila; Rami Rahmani; Khaled Alouani (International Journal of Analytical Chemistry)
Rumex crispus L. (R. crispus) is regarded as an aromatic plant. It was used for its excellent biological properties in traditional medicine. The aerial part was extracted successively by maceration with three solvents increasing polarity (cyclohexane (CYH), dichloromethane (DCM), and methanol (MeOH)) to evaluate their chemical compositions and biological activities. The extracts were rich in phenolic compounds (13.0 to 249.8 mg GAE/g of dry weight (dw)). The MeOH extract has presented remarkable IC50 = 6.2 μg/mL for anti-DPPH and 31.6 μg/mL for anti-AChE. However, the DCM extract has the highest cytotoxic activity against the two cancer cells (HCT-116 and MCF-7) (69.2 and 77.2% inhibition at 50 μg/mL, respectively). Interestingly, GC-MS analysis enabled to identify three new compounds in R. crispus extracts, such as L-(−)-arabitol (5), D-(−) fructopyranose (7) detected only in MeOH extract, and 2, 5-dihydroxyacetophenone (3) detected in all extracts. For HPLC chromatograms, cardamonin (8), 5-hydroxy-3′-methoxyflavone (17), and 3′-hydroxy-b-naphthoflavone (18) showed the highest concentrations of 74.0, 55.5, and 50.4 mg/g of dw, respectively, among others who are identified. Some phenolic compounds were identified and quantified by HPLC in more than one organic extract, such as 4′, 5-dihydroxy-7-methoxyflavone (13), 4′, 5-dihydroxy-7-methoxyflavone (14), 5-hydroxy-3′-methoxyflavone (17), and 3′-hydroxy-b-naphthoflavone (18), were found for the first time in the R. crispus extracts. Our results showed that the biological activities of this plant might be linked to their phenolic compounds and that the polar extracts could be considered as new natural supplements to be used in food and pharmaceuticals.